Sistem Pemilihan Modalitas Belajar Siswa Berbasis Website Menggunakan Metode Simple Additive Weighting di MA As Sakinah - Waluyo, Iwan Giri; Savitri, Savitri; Hidayati, Tri (Scientia Sacra: Jurnal Sains, Teknologi dan Masyarakat, 2025)
In the current digital era, the diversity of learning modalities available provides challenges for students in choosing the learning method that best suits their needs. To overcome this, this research developed a website-based student learning modality selection system that uses the Simple Additive Weighting (SAW) method. This system is designed to assist students in determining optimal learning modalities based on several relevant criteria, such as learning style and learning effectiveness capabilities. The SAW method was chosen because of its ability to provide objective decision results through the sum of the weights of each predetermined criterion. The research results show that this system can facilitate students in selecting appropriate learning modalities, thereby increasing the effectiveness of the overall learning process. It is hoped that the implementation of this system can make a positive contribution to the world of education by utilizing technological information to support a more adaptive and personalized learning process.